Diversity studies on insect pests of high altitudinal transitional zones of North-western Himalayas - PAWAN KUMAR; TAMANNA SINGH THAKUR; DEEPIKA DEEPIKA; NEHA SHARMA (Smujo International, 2022)
Abstract. Kumar P, Thakur TS, Deepika, Sharma N. 2022. Diversity studies on insect pests of high altitudinal transitional zones of North-western Himalayas. Nusantara Bioscience 14: 203-210. Class Insecta constitute a major fauna and comprise many species of economic importance. Due to climate change and increase in temperature, many insect species are changing their habitat considerably and shifting their hosts, which leads to changes in the diversity of insect pests at different altitudinal gradients. High altitude forest cover is not large and massive as plains forest cover, but it supports some of the very important economical tree species like- Quercus sp., Himalayan Poplar, Betula sp., Abies pindrow (Royle ex D.Don) Royle, Juniper spp., Birdcherry, Maple, etc. The present study analyzed any change in insect pest incidences and diversity of pest species due to the change in host preferences or climatic patterns. The study was conducted at four selected sites viz. Rohtang area (Kullu Forest Division), Chanshal area (Rohru Forest Division), Sach area (Churah Forest Division), and Indrahar area (Dharamshala Forest Division) of high altitudinal transitional zones of Himachal Pradesh, India, to study insect pest diversity. A total of 32 insect species were recorded during the study period comprised of the insect orders viz., Coleoptera, Hymenoptera, Hemiptera, Orthoptera, Dermaptera, and Lepidoptera. The present investigation led to the finding that species of Coleoptera (beetles) were the most dominant insects attacking trees of the high altitudinal transitional zone, followed by Lepidoptera (Butterflies and moths) and Hemiptera (aphids).